Does Technostress Impact On University Students’ Academic Performance in the New Normal? - Dilith Ranura Perera (International Journal of Engineering and Management Research, 2021)
Technostress is a critical disease in the current competitive environment experienced by all of us with the rapid enhancement in technology. COVID-19 pandemic has changed people’s lives to blend more with technology. Earlier, organizations and employees used more technology compared to school & university students. But now students have to use technology to do their studies, maintain their association with friends and to spend their leisure time as well. Moreover, every private and public educational institute is converting into online learning and teaching. Specially, all government universities are conducting lectures and assessments using technology. Even though this technology enables us to continue all our daily routines, it has a dark side that we need to examine. The purpose of this paper is to discuss about the technostress and its impact on academic performance among university students in Sri Lanka. Technostress is defined as a common problem of adaptation that may occur if the user is unable to adapt to, or work effectively with information and communication technology. This is vastly visible in government universities because there are many students who have stepped into the university representing both rural and urban areas in Sri Lanka. Technostress consists of several dimensions, including Techno-overload, Techno-invasion, Techno-complexity, Techno-insecurity, and Techno-uncertainty. There is a lack of empirical studies from the Sri Lankan context in relation to technostress and academic performance hence it is vital to examine the prevalence of technostress among undergraduates and postgraduates in Sri Lankan universities. This study therefore aims to provide researchers and practitioners a meaningful understanding of the university students’ technostress and its influence on academic performance in the new normal.